Water shortages, irrigation frequency, and preference for technologies and agricultural services: the case of Jordan - Balasubramanya, Soumya; Stifel, David; McDonnell, Rachael (Wiley, 2022)
The use of improved technologies has been encouraged to improve irrigation on farms, especially in drought-prone areas. However, farmers' irrigation decisions may be rather motivated by a desire to reduce risk of crop loss than to reduce water use. Using the case of Jordan, we contribute to the water-saving debate by examining whether current irrigation frequency is influenced by past experiences of losses due to water shortage and whether preferences for technologies and irrigation advisory services are mediated by water shortage experiences. Our data are based on a survey of 304 fruit farms in the highlands that were all using drip irrigation, a popular way to “save” water globally. We find that farms that faced losses due to water shortages in the past are more likely to irrigate more frequently. More frequent irrigators who have such shortages are more likely to prefer receiving irrigation advisory information rather than upgrading technologies, while more frequent irrigators who have not faced such shortages are more likely to prefer upgrading irrigation technologies. Results suggest that irrigation management is motivated by risk reduction, not just by water conservation. Irrigation advisory services, hitherto neglected, may be an important component of agricultural water management in Jordan.